Reduced cerebellar diameter in very preterm infants with abnormal general movements - Spittle, A.; Doyle, L.; Anderson, P.; Inder, T.; Lee, K.; Boyd, Roslyn; Cheong, J. (Elsevier Ireland Ltd, 2010)
Background: Abnormal General Movements (GMs) early in life are predictive of later neuromotor deficits and are related to white matter abnormalities on magnetic resonance imaging (MRI). However, other structural correlates of abnormal GMs have not been defined. Aims: The objective of this study was to explore brain-metrics (linear brain measurements on MRI representative of 3-D brain volumes) at term as a predictor of abnormal GMs at 1 and 3. months' corrected age in preterm infants. It was hypothesized that abnormal GMs would be related to reduced brain-metrics in primary motor areas, namely the cerebellum and parietal lobes. Study design: Eighty three preterm infants (<30. weeks' gestational age) were scanned at term-equivalent age. MRI was assessed for white matter abnormality and brain-metrics in six predefined brain regions (i.e. bifrontal, biparietal, lateral ventricles and transverse cerebellar diameters, and inter-hemispheric distance). Outcome measures: At 1 and 3. months' corrected age infants' GMs were assessed from video-taped footage and rated as normal or abnormal using standardized methodology. Results: At 1. month, 63% (n=52) of infants had abnormal GMs with no association between any of the brain-metrics and abnormal GMs. At 3. months, 23% (n=18) of infants had abnormal GMs (absent fidgety movements n=18; abnormal fidgety movements n=0). Reduced bifrontal, biparietal, and cerebellar transverse diameters, along with an increase in lateral ventricle sizes were associated with an increased risk of abnormal GMs at 3. months' corrected age. After controlling for white matter abnormality and grade III/IV intraventricular haemorrhage, only the cerebellar transverse diameter was predictive of abnormal GMs at 3. months. Conclusions: Reduced cerebellar diameter at term equivalent age is related to abnormal GMs at 3. months' corrected age, independent of white matter abnormality and intraventricular haemorrhage. © 2009 Elsevier Ireland Ltd.